Structured Multiple Endosymbiosis of Bacteria and Archaea in a Ciliate from Marine Sulfidic Sediments: A Survival Mechanism in Low Oxygen, Sulfidic Sediments? - Edgcomb, Virginia P.; Leadbetter, Edward R.; Bourland, William; Beaudoin, David; Bernhard, Joan (Frontiers in Microbiology, 2011)
Marine micro-oxic to sulfidic environments are sites of intensive biogeochemical cycling and elemental sequestration, where prokaryotes are major driving forces mediating carbon, nitrogen, sulfur, phosphorus, and metal cycles, important from both biogeochemical and evolutionary perspectives. Associations between single-celled eukaryotes and bacteria and/or archaea are common in such habitats. Here we describe a ciliate common in the micro-oxic to anoxic, typically sulfidic, sediments of Santa Barbara Basin (California, USA). The ciliate is 95% similar to Parduzcia orbis (18S rRNA). Transmission electron micrographs reveal clusters of at least three different endobiont types organized within membrane-bound sub-cellular regions. CARD-FISH and 16S rRNA clone libraries confirm the symbionts include up to two sulfate reducers (Desulfobulbaceae, Desulfobacteraceae), a methanogen (Methanobacteriales), and possibly a Bacteroidete (Cytophaga) and a Type I methanotroph, suggesting synergistic metabolisms in this environment. This case study is discussed in terms of implications to biogeochemistry, and benthic ecology.